PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN GURU MELALUI EMPLOYEE ENGAGEMENT DI SMP SUBRAYON 09 KOTA SEMARANG [THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICE AND PERCEIVED ORGANIZATIONAL SUPPORT TOWARDS TEACHER COMMITMENT THROUGH EMPLOYEE ENGAGEMENT IN JUNIOR HIGH SCHOOL SUBRAYON 09 SEMARANG CITY] - Riady, Stephanie; Taryo; Sudibjo, Niko (Polyglot, 2025)
Success in developing schools cannot rely solely on external factors such as budget, technology, and physical facilities. Internal factors, particularly teachers' commitment to their profession and institution, play a key role in fostering a high-quality learning environment. Teachers with strong commitment are more likely to take initiative, be responsible, and contribute sustainably to achieving educational goals, making them a fundamental pillar of overall school progress. This study aims to examine the influence of human resource management practices and perceived organizational support on teacher commitment, with employee engagement as a mediating variable. The research was conducted at Junior High Schools in Subrayon 09, Semarang City, involving a sample of 194 teachers. Data were collected using a 5-point Likert scale questionnaire distributed online via Google Forms. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings indicate that human resource management practices and perceived organizational support have a positive effect on employee engagement and teacher commitment. Furthermore, employee engagement directly influences teacher commitment and significantly mediates the effect of human resource management practices and perceived organizational support on teacher commitment. Abstrak Bahasa Indonesia Keberhasilan dalam mengembangkan sekolah tidak cukup hanya mengandalkan faktor-faktor eksternal seperti anggaran, teknologi, dan fasilitas fisik. Faktor internal, khususnya komitmen guru terhadap profesi dan institusi, memegang peranan kunci dalam menciptakan lingkungan belajar yang berkualitas. Guru yang memiliki komitmen tinggi akan lebih berinisiatif, bertanggung jawab, dan berkontribusi secara berkelanjutan dalam mencapai tujuan pendidikan, sehingga menjadi fondasi utama dalam kemajuan sekolah secara menyeluruh. Studi ini bertujuan untuk meneliti pengaruh praktik manajemen sumber daya manusia dan perceived organizational support terhadap komitmen guru dengan employee engagement sebagai variabel mediasi. Objek yang dijadikan tempat penelitian yaitu SMP di Subrayon 09 Kota Semarang dengan sampel sebanyak 194 guru. Pengumpulan data menggunakan kuesioner skala Likert 5 poin yang didistribusikan secara online melalui Google Forms. Analisis data menggunakan Structural Equation Modeling berbasis Partial Least Squares (SEM-PLS). Temuan penelitian menunjukkan bahwa praktik manajemen SDM dan perceived organizational support berpengaruh positif terhadap employee engagement dan komitmen guru. Employee engagement juga terbukti secara langsung memengaruhi komitmen guru dan dapat secara signifikan memediasi pengaruh praktik manajemen SDM dan perceived organizational support terhadap komitmen guru